Meningitis retention syndrome associated with complicated mild encephalitis/encephalopathy with reversible splenial lesion in a young adult patient: a case report. Issue 10 (26th October 2021) - Hidaka, Masaoki; Sawamura, Natsuki; Yokoi, Mio; Mezuki, Satomi; Osaki, Masato; Arakawa, Shuji; Akiyama, Tomoaki; Yamaguchi, Shinya; Sayama, Tetsuro; Kitazono, Takanari
ABSTRACT: Meningitis retention syndrome (MRS), comprising aseptic meningitis and urinary retention, is a self-limiting disease that resolves within a few weeks. Refractory urinary retention and encephalitic syndromes are rare. A 32-year-old man presented with acute fever and headache followed by acute urinary retention (UT). Neurological examination revealed meningeal irritation, UT, constipation and ataxic gait. The cerebrospinal fluid showed mononuclear leukocytosis, and the etiological examination was negative. We suspected MRS. However, magnetic resonance imaging demonstrated an abnormally intense lesion in the splenium of the corpus callosum (SCC). He also developed delirium on day 4 of hospitalization. We diagnosed the patient with MRS associated with mild encephalitis/encephalopathy with a reversible splenial lesion (MERS). While his delirium and constipation improved, and the SCC lesion disappeared, UT was refractory and required 6 months to complete recovery. Our case suggests that severe MRS can exhibit refractory UT and may associate with MERS.